Optoelectronic properties of oligomers based on tetrazine, benzothiadiazole, benzodithiophene and thiophene moieties for photovoltaic applications: a theoretical study. Issue 102 (5th October 2015) - Ottonelli, Massimo; Alloisio, Marina; Moggio, Ivana; Martinez Espinosa, M. Isabel; Arias, Eduardo
Abstract : In this article, a fast theoretical design approach for addressing the synthesis of new conjugated co-polymers for applications in organic photovoltaic devices is discussed. Abstract : Herein, a theoretical design addressed to the synthesis of new conjugated co-polymers for organic photovoltaic devices based on tetrazine, benzothiadiazole, dithiophene and thiophene moieties has been applied. This theoretical investigation aims to explore which combination of these molecules could be the most promising for photovoltaic applications, by studying their intrinsic electronic properties. In particular, the simulated values of the band gap energy and the open circuit voltage are the parameters to be taken into account for the selection of potential materials for solar cell devices. The results shows that the most suitable combination, giving rise to low band gaps, higher absorption coefficients and with an interesting offset of the HOMO and LUMO energy levels, is the bridge-linked copolymer which alternates the benzodithiophene and the benzothiadiazole moieties, likely because of their push–pull effect.